Substituição do ligamento redondo femoral por “loop” pediculado de fáscia lata em cães - Moya , Luz Eliana Guaimás (2001)
The present study has for objective the evaluation of a surgical method for treatment of traumatic hip dislocations in dogs, stabilizing the coxofemoral articulation by the replacement of the round femural ligament using the fascia lata. For this experiment 18 adult dogs, without defined race, males and females, were used, separate in three groups according to corporal weight. The stabilization was obtained for loop of fascia lata inserted from the third trochanter, emerging in the fóvea capitis and through the acetabulum, returning to the insert point. In none of the cases was used immobilization after surgery. Walking movement was daily evaluated and articulations were macroscopically observed at 60 and 90 days of postoperative. Two animals didn't weightbear the operated member during the immediate postoperative, but total recover was not affected. Other animals of groups A, B and C weightbeared the member at immediate postoperative and the total recover was at 15,5, 18 and 16,5 days, respectively. These experiment´s results show that the surgical technique proposed allows to maintain the articulate stability, with an early weightbearing and relatively short period of functional use of the member.